2010
DOI: 10.1111/j.1600-0897.2009.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Suppression of Natural Killer Cell Cytotoxicity in Postpartum Women

Abstract: Problem-Natural Killer (NK) cell numbers and cytotoxicity are suppressed during pregnancy. Little is known about postpartum NK number and function.Method of study-Postpartum women (n = 39) were studied at one week and then monthly over the first six postpartum months. The standard natural killer cell cytotoxicity assay (NKCA) was performed. This is a Cr51 release assay from K562 cells cultured with peripheral blood mononuclear cells (PBMCs).Results-Data indicate suppression of NK cytotoxicity in postpartum wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
(25 reference statements)
0
11
1
Order By: Relevance
“…In the present study NK activity was measured using flow cytometry and FITC-or CFDA-labeled K562 target cells. According to the present results, no difference in cytotoxicity was observed between MPB and CB samples, in contrast to studies that reported suppression of NK cell cytotoxicity in postpartum women [48]. The same suppression pattern was observed in NK cells from premature infants, as compared to those from full-term infants [49][50][51], indicating that not only the number, but also the function differs according to the type of delivery.…”
Section: Akdeniz Et Al Differences In Cord Bloodcontrasting
confidence: 55%
“…In the present study NK activity was measured using flow cytometry and FITC-or CFDA-labeled K562 target cells. According to the present results, no difference in cytotoxicity was observed between MPB and CB samples, in contrast to studies that reported suppression of NK cell cytotoxicity in postpartum women [48]. The same suppression pattern was observed in NK cells from premature infants, as compared to those from full-term infants [49][50][51], indicating that not only the number, but also the function differs according to the type of delivery.…”
Section: Akdeniz Et Al Differences In Cord Bloodcontrasting
confidence: 55%
“…Increased HIV-1 risk during pregnancy could reflect a higher frequency of unprotected sexual activity among women who become pregnant versus those who do not become pregnant or could be caused by biologic changes in pregnancy and the postpartum period, such as immunologic changes affecting both the adaptive and innate immune systems [20, 23], that may facilitate HIV-1 transmission. We found the risk for female-to-male transmission was statistically significant after adjustment for confounding factors and may thus primarily reflect biological changes of pregnancy that may increase HIV-1 infectiousness.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier cross-sectional study of 200 women at 4-6 weeks postpartum, we found that the NK cell number was reduced compared to controls (Groer et al, 2005). With regard to NK functional activity, we previously reported that NK cytotoxicity was reduced through 6 postpartum months in a small sample of 39 women being measured in a larger study of postpartum immunity (the parent study; Groer, El-Badri, Djeu, Harrington, & Van Eepoel, 2010). We conceptualized this reduced NK cytotoxicity in the postpartum period to be a continuation of pregnancy-induced NK cytotoxicity suppression, proposing that it could possibly facilitate tolerization of fetal microchimeric cells to survive and establish themselves in tissue niches (Groer, Manion, Szekeres, & El-Badri, 2011).…”
mentioning
confidence: 82%
“…Without this IL-2 preincubation, the cytotoxicity of these postpartum NK cell cultures was extremely low or nonexistent. The PBMCs were then cocultured the next day with 100 mg of CiCr 51 -labeled K562 cells for 5 hr for the NKCA, as reported previously (Groer et al, 2010). NK cytotoxicity data are reported as LUs or as percentage cytotoxicity at the 50:1 effector:target (E: T) ratio depending on the experiment.…”
Section: Assessments and Measuresmentioning
confidence: 99%